Academic Senate Minutes 2004-10-28 - Academic Senate:::::::::
Chair's report. Agenda amended and approved. Minutes of 10/14/04 approved. Academic Affairs Strategic Planning document second reading. Procedures for Faculty Trustee Nominations – motion to amend something previously adopted approved. Endowed Chairs Policy first reading. Withdrawal Policy first reading. Provost report including annual report of the Office of Research and Sponsored Programs.